Autonomic management of non-functional concerns in distributed & parallel application programming - Aldinucci, M.; Danelutto, M.; Kilpatrick, P. (2009 IEEE International Symposium on Parallel & Distributed Processing, 2009)
An approach to the management of non-functional concerns in massively parallel and/or distributed architectures that marries parallel programming patterns with autonomic computing is presented. The necessity and suitability of the adoption of autonomic techniques are evidenced. Issues arising in the implementation of autonomic managers taking care of multiple concerns and of coordination among hierarchies of such autonomic managers are discussed. Experimental results are presented that demonstrate the feasibility of the approach.